Fundamental Analysis of Car Manufacturing Companies in India for 1.4.2005 to 31.3.2016 - Soni, Shriprakash; Chandak, Govind (International Research Journal of Management, IT & Social Sciences, 2017)
The most important strength in todayâs volatile financial market is information. Investors always confused on the information as to where to invest, when to invest and how much to invest their money. Generally, the information derives from market or some different sources. To act on this information, analysts, experts, and researchers start researching whether the information has positive or negative impact. At individual level, an investor can also do the fundamental analysis, which will give him a better foundation for his investment decisions. This analysis helps investors in taking decision. If investor will take decision based on wrong information, the losses incurred could be tremendous and harmful and the recovery of the investment can take a lot of time or sometimes it can be irrecoverable. Hence, investors should spend a sizable amount of time for scrutinizing financial position of the company, shares of the company and calculating estimations of the same. The fundamental analysis helps to understand the patterns in companyâs financial performance. One can easily predict the future performance based on fundamental analysis by using financial statements. It is generally useful for long-term investment. As quoted by John Forman, âFundamental analysis is very powerful in terms of determining long-term direction, but lacks short-term applicabilityâ. The researchers used some of the important key variables for a period of 10 years i.e. from 2006-07 to 2015-16 for top five automobile companies (Car-Indian Manufacturing) namely TATA Motors DVR, Mahindra CIE Automotive, SML-Isuzu, Force India and Maruti Suzuki India. The researchers also compared the fundamentals of these 5 companies and applied different statistical tools.Â